Supporting Transgender Inclusion and Gender Diversity in Schools: A Critical Policy Analysis - Omercajic, Kenan; Martino, Wayne (Frontiers in Sociology, 2020)
In this article, we conduct a policy analysis of transgender affirmative policies in Ontario and examine their implications for addressing gender justice and gender democratization in the school system. By adopting a case study approach, we provide a critical analysis of these policies and of how stakeholders with familiarity and knowledge of trans-affirmative policies from two school boards in Ontario are making sense of their impact with respect to addressing trans inclusion in schools. As such, our study offers insight into two trans-affirmative policies and their implications for both supporting transgender, gender non-conforming and nonbinary students and envisioning gender-expansive education in the school system. We draw on interviews with key informants – two teachers and a school board official – as a basis for reflecting on the need to move beyond a discourse of accommodation in trans inclusive policies to one that explicitly articulates a pedagogical commitment to gender justice and gender democratization in schools.